An innovative cooperative model for the Master Degree Project of Architecture. Overcoming the traditional system. - Rosa-Jiménez, Carlos; Nebot-Gómez-de-Salazar, Nuria; García-Moreno, Alberto Enrique (Editorial Universitat Politècnica de València, 2017)
Although the Bologna’s process has highlighted the need to develop deep and structural changes in the educational institutions, there is a scarce bibliography on innovation projects in Master Degree Projects, specifically in the field of Architecture. This paper is part of a educational innovative reaserch project that is proposing a cooperative process-and-product model-based for MDP. The model is developed in three stages, from collaborative learning action groups to indivual project. At the end of the process the student has developed three documents: a presentation, a product and a daily-portfolio. Finally, MDP assessment is the sum of three evaluations
http://dx.doi.org/10.4995/HEAD17.2017.6713
Keywords: Arquitectura - Estudio y enseñanza; Proyecto Fin de Carrera; Arquitectura; Aprendizaje cooperativo